Managing historical legacies – Gwydyr Reservoirs. Issue 3 (20th September 2021) - Shaw, Darren; Coombs, Matthew; Basford, Andrew; Morris, Steven; Davies, Alun Rhys
Abstract : The changes to the Reservoir Act legislation in Wales, which were implemented in 2016, resulted in in the requirements for formal registration of a reservoir reducing from 25 000 m 3 capacity to 10 000 m 3 . This paper describes the process followed by Natural Resources Wales, as an owner, to identify and assess the newly registered assets. Llyn Cyfty, an early nineteenth century mining water supply reservoir within the Gwydyr Forest in north Wales, had a number of measures in the interests of safety (MITIOS) due to its poor condition. A case study is presented of essential emergency repairs during the 2015−2016 winter period, and the work undertaken to design and implement necessary permanent remedial works. These works included embankment stabilising and raising, and construction of a new spillway.